Effect of Growth Arrestment Disease on the Anatomy and Ultrastructure of Vitis vinifera L. var. sultana - De La Harpe, A. C.; Archer, E. (South African Journal of Enology and Viticulture, 2017)
The anatomical and ultrastructural changes caused by the so called Growth Arrestment Disease (G.A.D.) in Vitis vinifera L. var. sultana were investigated by means of scanning and transmitted electron microscopy as well as light microscopy. Important morphological symptoms are described. Anatomical abnormalities were found, especially in the leaves and Hower clusters of the affected vines. Heat and moisture stress may induce abnormal physiological changes, and this may give rise to G.A.D.-symptoms.